1956
DOI: 10.2136/sssaj1956.03615995002000020020x
|View full text |Cite
|
Sign up to set email alerts
|

Some Factors Influencing the Utilization of Phosphorus from Crop Residues

Abstract: A large proportion of phosphorus of crop residues was found to be readily available to succeeding crops. Some of the factors that influence the rate of release of phosporus from plant residues added to soils for use by succeeding plants were studied. They were: (a) maturity of the crop residue, (b) phosphorus content of the residue, (c) rate of application of the residues, (d) time of contact of the crop residue with the soil, (e) kind of crop residue, and (f) plant part involved. The study was conducted under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1966
1966
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…This would suggest that it was the loss of organic P from the soil and not from plant residues (as in the cultivated soils) that was the predominant pool involved, and furthermore that this pool of organic P is highly labile (water soluble). This is consistent with the wide C:P ratio of the plant residues, as it is suggested that for ratios > 300:1 (C:P) immobilisation occurs and for ratios < 200:1 (C:P) mineralisation occurs (Fuller et al 1956;Dalal 1977). Phosphorus from plant residues in our study would likely be immobilised (C:P ratio > 300, Table 3) before any mineralisation or release to drainage occurred.…”
Section: Discussionsupporting
confidence: 90%
“…This would suggest that it was the loss of organic P from the soil and not from plant residues (as in the cultivated soils) that was the predominant pool involved, and furthermore that this pool of organic P is highly labile (water soluble). This is consistent with the wide C:P ratio of the plant residues, as it is suggested that for ratios > 300:1 (C:P) immobilisation occurs and for ratios < 200:1 (C:P) mineralisation occurs (Fuller et al 1956;Dalal 1977). Phosphorus from plant residues in our study would likely be immobilised (C:P ratio > 300, Table 3) before any mineralisation or release to drainage occurred.…”
Section: Discussionsupporting
confidence: 90%
“…Further, earlier studies reported up to 40 % (McLaughlin et al 1988c) and 50 % (Friesen and Blair 1988) mineralisation of P from organic residues at 7 and 11 days. Although these earlier studies indicate that P release from young residues will be rapid (Fuller and Dean 1949;Fuller et al 1956), low mineralisation and release of P from the two legume residues (which were just 22 days older) in this study could possibly be due to the lack of distinct drying and wetting cycles (Chepkwony et al 2001). Transpirational demand was low and soil water content was permanently high, potentially slowing mineralisation significantly.…”
Section: Treatmentmentioning
confidence: 60%
“…Crop residues also contain a significant proportion of the nutrients taken up by the crop and, when returned to the soil, contribute to the maintenance of soil fertility. Several studies have shown that such materials can be an important supply of phosphorus (P) to subsequent crops (Blair and Boland, 1978;Dalal, 1979;Friesen and Blair, 1988;Fuller et al, 1956;Till and Blair, 1978). The rate and extent of reutilization of P from crop residues can be influenced by a number of factors including the amount and type of residues, their carbon : P (C : P) ratio and the prevailing soil and climatic conditions (Dalal, 1977).…”
Section: Introductionmentioning
confidence: 99%